Gambaran Kecakapan Hidup (Life Skill) Pada Remaja SMP Muhammadiyah 2 Di Surakarta - Sulistianingrum, Sulistianingrum; , Siti Arifah, SKp., M.Kes (2016)
Adolescence is a period of transition from childhood to adulthood. In adolescence, this has a very complex issue, along with a natural transition in adolescence. Therefore, the teenager as the nation's next generation need to be prepared for them health physical, spiritual, mental and spiritual. Life skills are the skills or the ability to be able to adapt and behave positively, which allows one to face the demands and challenges of everyday life effectively. The purpose of this study is to describe the life skills in adolescents SMP Muhammadiyah 2 Surakarta. Life skills include problem solving skills, creative thinking, critical thinking, self-awareness, make decisions, deal with emotions. The research method using descriptive. The population is class VIII and IX grade students with the number 353, therefore, the sampling technique used propotionate stratified random sampling in order to obtain a sample of 78 respondents. Data analysis using SPSS 20.0 with a measurement of the frequency distribution. The results showed that adolescents SMP Muhammadiyah 2 Surakarta as many as 66 respondents were able to resolve its own problems, 41 respondents were able to take a decision on family issues, 69 respondents were able to plan a study and his own career, 43 respondents were able to adjust the revenue and expenditure itself, 78 of respondents always saved, 76 respondents always buy everything as needed, 77 respondents always plan before doing something, 67 respondents constantly learn and adapt to the people who have opinions and different lifestyle, 74 respondents dare resist when a friend persuaded to break the rules, 64 respondents dare to resist risky behaviors (such as sex, drugs, violence, and bad media), 77 respondents were able to adapt if no unexpected events, and 65 respondents were able to control the situation when angry or when there are arguments. The conclution that the adolescent life skills SMP Muhammadiyah 2 in Surakarta generally good.